Why Did ZIKV Perinatal Outcomes Differ in Distinct Regions of Brazil? An Exploratory Study of Two Cohorts - Luana Damasceno; Ana Carolina B. Terzian; Trevon Fuller; Cassia F. Estofolete; Adriana Andrade; Erna G. Kroon; Andrea A. Zin; Zilton Vasconcelos; Jose P. Pereira; Márcia C. Castilho; Isa Cristina R. Piaulino; Nikos Vasilakis; et al. (Viruses, 2021)
The Zika virus (ZIKV) epidemic in Brazil occurred in regions where dengue viruses (DENV) are historically endemic. We investigated the differences in adverse pregnancy/infant outcomes in two cohorts comprising 114 pregnant women with PCR-confirmed ZIKV infection in Rio de Janeiro, Southeastern Brazil (n = 50) and Manaus, in the north region of the country (n = 64). Prior exposure to DENV was evaluated through plaque reduction neutralizing antibody assays (PRNT 80) and DENV IgG serologies. Potential associations between pregnancy outcomes and Zika attack rates in the two cities were explored. Overall, 31 women (27%) had adverse pregnancy/infant outcomes, 27 in Rio (54%) and 4 in Manaus (6%), p < 0.001. This included 4 pregnancy losses (13%) and 27 infants with abnormalities at birth (24%). A total of 93 women (82%) had evidence of prior DENV exposure, 45 in Rio (90%) and 48 in Manaus (75%). Zika attack rates differed; the rate in Rio was 10.28 cases/10,000 and in Manaus, 0.6 cases/10,000, p < 0.001. Only Zika attack rates (Odds Ratio: 17.6, 95% Confidence Interval 5.6–55.9, p < 0.001) and infection in the first trimester of pregnancy (OR: 4.26, 95% CI 1.4–12.9, p = 0.011) were associated with adverse pregnancy and infant outcomes. Pre-existing immunity to DENV was not associated with outcomes (normal or abnormal) in patients with ZIKV infection during pregnancy.